1961
DOI: 10.1002/aja.1001090204
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of gastric mucosa in rats

Abstract: 2841 C1) and the Upjohn Company. 2Based on a dissertation submitted in partial fulfillment of the requirements for the Doctor of Philosophy degree. 3 This investigation was carried out during the tenure of a Predoctoral Fellowship from the National Cancer Institute, United States Public Health Service. Deep appreciation is extended to Dr. Burton L. Baker for his direction of this investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
12
0

Year Published

1966
1966
1994
1994

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(18 citation statements)
references
References 15 publications
6
12
0
Order By: Relevance
“…The chief cells have been suggested by some authors to arise from undifferentiated cells in the isthmus of the gland (KATAOKA, 1970;WILLEMS and LEHY, 1975), while assumed by others to be derived from mucous neck cells (MENzIES, 1958;TOWNSEND, 1961;HATTORI, 1974;HATTORI and FUJITA, 1976;WATTEL et al, 1979). In addition, some investigators reported that the chief cells are capable of self-replication (CHEN and WITHERS, 1975;WILLEMS and LEHY, 1975;HATTORI and FUJITA, 1976), whereas some others have shown the absence of 3H-thymidine (3H-TdR~ label over the cells (HUNT, 1957;LIPKIN et al, 1963;LAWSON, 1970;WATTEL and GEUZE, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The chief cells have been suggested by some authors to arise from undifferentiated cells in the isthmus of the gland (KATAOKA, 1970;WILLEMS and LEHY, 1975), while assumed by others to be derived from mucous neck cells (MENzIES, 1958;TOWNSEND, 1961;HATTORI, 1974;HATTORI and FUJITA, 1976;WATTEL et al, 1979). In addition, some investigators reported that the chief cells are capable of self-replication (CHEN and WITHERS, 1975;WILLEMS and LEHY, 1975;HATTORI and FUJITA, 1976), whereas some others have shown the absence of 3H-thymidine (3H-TdR~ label over the cells (HUNT, 1957;LIPKIN et al, 1963;LAWSON, 1970;WATTEL and GEUZE, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the mucous neck cells are the precursors of chief cells, and that they are converted to chief cells via intermediate cells, which have characteristics of both mucous neck cells and chief cells (Townsend, 1961;Hunt and Hunt, 1962;Helander, 1969;Hattori and Fujita, 1976;Tamura and Fujita, 1983;Suzuki et al 1983;Cornaggia et al 1986; Ihida et al 1988; Kantani and Kataoka, 1989;Madrid et al 1990) In general, mucous neck cells are considered histochemically to be cells that stain positively for the PAS reaction, the GSA II reaction and upon paradox staining by Con A (Sheahan and Jervis, 1976;Wattel and Geuze, 1977;Katsuyama and Spicer, 1978;Ihida et al 1988). We reported that two types of mucous neck cell [containing alcian blue (pH 2.5) positive acidic mucin or containing hematoxylin (pH 6) positive neutral mucin (Akita et al 1985)1 can be observed in the region close to the cardia (Kaneko et al 1987).…”
mentioning
confidence: 99%
“…Except for irregular proliferation observed in one case each of groups BC and BHC, the mode of epithelial regeneration of ulcers with cicatricial healing was quite similar to that of experimental gastric ulcers reported by others. 7,8 On the other hand, deep epithelial proliferation from the margin of chronic penetrating ulcer into the callous tissue beneath the ulcer was frequently observed. Such deep epithelial proliferation of chronic ulcers was found in about half the cases of groups B and BH (not receiving the carcinogen) on examination 60 days or more after operation, but on these occasions the proliferation was mild in grade and localized to the ulcer margin.…”
Section: ) Gross and Microscopic Findings 60 And 120 Days After Opermentioning
confidence: 99%